PUTUSAN NO (NIET ONTVANKELIJK VERKLAARD) TERHADAP PERBUATAN WANPRESTASI - Suhendar (Yustitia, 2019)
This research was conducted in Indramayu Regency, precisely in Indramayu District Court by conducting direct interview in Indramayu District Court as a basis for comparison and a basis for reference in answering research questions. In addition to the field research, the researcher also conducts literature studies by reading, analyzing, and gathering information from books, literature, laws and other supporting regulations that have relevance to the issues discussed in this study. This research used empirical juridical research method, which is based on the study of legal materials and interviews as a process to find the rule of law and legal principles, in order to answer the legal problems encountered. This study intended to determine the implementation of the award which states that the lawsuit could not be accepted as well as the basis of the judge's judgment in the decision with the lawsuit that is not accepted regarding the the case Number; 35/Pdt.G/2014/PN.Idm. concerning acts of default in the Indramayu District Court. The results obtained by the researcher through this study are (1) the implementation of the verdict with a lawsuit is not acceptable (Niet Ontvankelijk verklaard) regarding Case Number 35/Pdt.G/2014/PN.Idm. The verdict with an unacceptable lawsuit is the fault of the plaintiff in formulating the lawsuit. It is also become part of the court's negligence in implementing the mandate of Article 119 HIR/143 Rbg of the constitution which authorizes the head of the district court to give advice and assistance to the parties to prevent the imperfect claim.